2004
DOI: 10.1016/j.cell.2004.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Mdm2-Mediated NEDD8 Conjugation of p53 Inhibits Its Transcriptional Activity

Abstract: The only reported role for the conjugation of the NEDD8 ubiquitin-like molecule is control of the activity of SCF ubiquitin ligase complexes. Here, we show that the Mdm2 RING finger E3 ubiquitin ligase can also promote NEDD8 modification of the p53 tumor suppressor protein. Mdm2 is itself modified with NEDD8 with very similar characteristics to the autoubiquitination activity of Mdm2. By using a cell line (TS-41) with a temperature-sensitive mutation in the NEDD8 conjugation pathway and a p53 mutant that canno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
462
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 495 publications
(477 citation statements)
references
References 56 publications
12
462
0
3
Order By: Relevance
“…Finally, Pin1 stimulates acetylation of p53 and p73 by p300 and dissociation from the inhibitor iASPP, thus enhancing the transcriptional activity of p53 and p73 towards proapoptotic target genes catalyzing its NEDDylation. 65 It will be interesting to determine whether Pin1 activity can also affect the pathways, yet elusive, which engage the p53 DNA-binding domain with the ubiquitin ligases Pirh2 and COP1. 66,67 p53 transcriptional activity is also regulated by interaction with acetyltransferases and stress-activated isomerization of p53 stimulates the acetylation of p53 C-terminal lysine residues by p300/CBP (G Del Sal, unpublished data), analogous to p73.…”
Section: The Prolyl Isomerase Pin1mentioning
confidence: 99%
“…Finally, Pin1 stimulates acetylation of p53 and p73 by p300 and dissociation from the inhibitor iASPP, thus enhancing the transcriptional activity of p53 and p73 towards proapoptotic target genes catalyzing its NEDDylation. 65 It will be interesting to determine whether Pin1 activity can also affect the pathways, yet elusive, which engage the p53 DNA-binding domain with the ubiquitin ligases Pirh2 and COP1. 66,67 p53 transcriptional activity is also regulated by interaction with acetyltransferases and stress-activated isomerization of p53 stimulates the acetylation of p53 C-terminal lysine residues by p300/CBP (G Del Sal, unpublished data), analogous to p73.…”
Section: The Prolyl Isomerase Pin1mentioning
confidence: 99%
“…The murine double minute 2 (Mdm2) oncogene product is a major regulator of p53 function and as an E3-ligase controls p53 modification with Ub and Ubls. In particular, Mdm2 has a dual specificity for Ub and NEDD8 and can promote p53 modification with both molecules (Xirodimas et al, 2004). Although Mdm2 can promote ubiquitination and degradation of p53 in both nucleus and cytoplasm (Xirodimas et al, 2001b), it is suggested that the levels of Mdm2 can have a differential effect on p53 ubiquitination with distinct biological outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…These lysine residues are also the potential ubiquitination sites. Importantly, NEDDylation appears to have a negative impact on the transactivation activity of p53 (Xirodimas et al, 2004). We show that 14-3-3s can antagonize MDM2-mediated p53 NEDDylation, which in turn will take away the inhibitory effect of NEDDylation on p53 transcriptional activity.…”
Section: Discussionmentioning
confidence: 78%
“…In addition to ubiquitination activity, MDM2 uses its C-terminal RING domain to promote p53 NEDDylation at three lysine residues of p53 (Xirodimas et al, 2004). These lysine residues are also the potential ubiquitination sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation